COMPARATIVE ASSESSMENT OF THE QUALITY OF LIFE OF PATIENTS WHO UNDERWENT FOOT AMPUTATION WITH FOOD DIABETIC SYNDROME: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Matmurotov, K.Zh.; Ruzmetov, B.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The presented convincing data once again proves that modified foot amputation improved the quality of life of patients after foot amputation in patients with FDS.